A Physical Charge-Based Analytical Threshold Voltage Model for Cryogenic CMOS Design - Hao Su; Yiyuan Cai; Shenghua Zhou; Guangchong Hu; Yu He; Yunfeng Xie; Yuhuan Lin; Chunhui Li; Tianqi Zhao; Jun Lan; Wenhui Wang; Wenxin Li; et al. (IEEE Journal of the Electron Devices Society)
This paper proposes a physical charge-based analytical MOSFET threshold voltage model that explicitly incorporates interface-trapped charges which have been identified as playing a dominant role in defining threshold voltage trends in deep cryogenic temperatures. The model retains standard threshold voltage definition by various charges across the MOSFET capacitor while being analytical in its form, therefore, suitable for cryogenic CMOS VLSI design. Consequently, a model covering each and all above characteristics is proposed for the first time. Excellent fit between the model and measurement data from 180-nm bulk foundry devices is shown from room temperature to 4 K.